Solar water heater with spoiler - MA LI; ZUO HONGRUI; FAN XUEJIAO; ZHANG ZIBIN; LIU CHUNHUA; HU SHUIHONG (2018)
The invention discloses a solar water heater with a spoiler. The solar water heater comprises a solar heat collector, a cold water tank, a hot water tank and a support; the solar heat collector comprises a frame and a plurality of solar vacuum heat collecting tubes which are arranged in the frame in parallel; the frame comprises a top plate, a bottom plate and side plates on the two sides; and thetop plate and the bottom plate are correspondingly provided with inserting holes which are used for penetrating through the solar vacuum heat collecting tubes. 本发明公开了种带扰流器的太阳能热水器，包括太阳能集热器、冷水箱、热水箱以及支架，所述太阳能集热器包括框架以及设置在所述框架内的多根并排平行排列的太阳能真空集热管，所述框架包括顶板、底板以及两侧的侧板，在所述顶板与底板上设置有相对应的用于穿过所述太阳能真空集热管的插孔。